Behavior of safflower elite lines high productivity and oil quality in the Yaqui Valley, Sonora, Mexico - Aguilera Molina, Néstor Alberto; Hernández Juarez, Agustin; Montoya Coronado, Lope; Aguirre Uribe, Luis Alberto; Cerna Chávez, Ernesto; Landeros Flores, Jerónimo (Revista Mexicana de Ciencias Agrícolas, 2021)
The safflower Carthamus tinctorius L. it is a crop that has been adopted by a large number of producers, particularly in the Northwest of the country, due to its great adaptability and its little water requirement, due to the great demands presented by the oilseed industry in the country. Since the 1970s it has been worked to generate materials that are highly productive, with good percentage and qualityof oil and with characteristics of resistance to the main diseases present in the region (false mildew and leaf rust). For this reason, the objective of this work was to evaluate the behavior of the elite safflower lines generated by the genetic improvement program in the region (23 oleic and 1 linoleic). These lines were established during cycles 2017-2018 and 2018-2019. Its agronomic behavior was evaluated under the present conditions of the Yaqui Valley. Oleic lines were found that surpassed witnesses Ciano ol and Chey ol, varieties that are widely sown in the region. In addition, it was found that the linoleic type line had better agronomic characteristics, production and oil content than witness RC-1002 which leads to the conclusion that within the evaluated lines there are potential materials to be released as a variety.